Librational motion of CO in solid Ar: Raman and IR spectra and quantum simulations - Lindgren, Johan; Olbert-Majkut, Adriana; Pettersson, Mika; Kiljunen, Toni (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
Rovibrational Raman spectra of CO molecules isolated in solid Ar were measured for the 9–30 K temperature range and compared to past and present IR spectra. The fundamental band appears as a triplet-split structure, where the center peak shows completely different response to temperature in the Raman and IR spectroscopies. The peak is sharp and stable in Raman but reversibly broadens beyond recognition in IR upon annealing. The red-shifted, intense line of the triplet is found thermally inert similarly in both spectroscopies. The third line is the weakest, and as concentration dependent, it is assigned to a dimer as before. The CO–H2O impurity complex is identified as a side band. We employ crystal field and quantum chemical modeling to interpret the disparity between the spectroscopies. The stable and broadening lines are given assignments to double- and singlesubstitution sites, respectively. Thermal excitations are not effective in the former case of angularly tightconfined, deep potential well. In the single-substitutional case, the librational level structure shows up in discriminating between the Raman and IR selection rules. An effectively ΔJ = 0 totally symmetric transition is found for Raman that is uncoupled from lattice phonons and corresponding broadening mechanisms. The low-temperature limit necessitates the use of a fixed lattice approach while the warmer end of the range is best described with an adiabatic, pseudorotating lattice approach.